2005 6th International Conference on Electronic Packaging Technology
DOI: 10.1109/icept.2005.1564698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Testing Conditions and Multiple Reflows on Cold Bump Pull Test of Pb-free Solder Balls

Abstract: Ball pull test has emerged to be an attractive alternative to the traditional ball shear testing method for characterizing the attachment strength of solder interconnection. Since this is a relatively new development, so far there is no industrial standard to regulate this testing method. In this study, the pull and shear tests are performed on plastic ball grid array (PBGA) solder balls with Sn-4.0Ag-0.5Cu and Sn-37Pb solders, subject to a wide variety of testing conditions. To investigate the material sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, from previous research results [4], it seems that the ball shear test cannot correlate the degradation of ball shear strength to the growth of IMC thickness too well. This phenomenon should be due to the fact that IMCs are not that weak under the shear loading.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, from previous research results [4], it seems that the ball shear test cannot correlate the degradation of ball shear strength to the growth of IMC thickness too well. This phenomenon should be due to the fact that IMCs are not that weak under the shear loading.…”
Section: Introductionmentioning
confidence: 87%
“…Firstly, the interface usually appears to be weaker in tension than in shear. Secondly, the failure in tensile as opposed to shear loading, is little influenced by solder mask interference and gross deformation of the solder [4,5].…”
Section: Ball Shear and Ball Pull Tests After Thermal Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table1, it shows the testing parameters and related materials. In the pin pull/ball pull test, both the testing condition and the thermal history of the testing samples were varied in order to get a comprehensive assessment on the testing method [9,10]. Since the NSMD pad opening was used, after the test, it was found that the pad crater was the only failure mode appeared in all the tests.…”
Section: Comparison Between Cold Pin Pull and Ball Pull Testmentioning
confidence: 99%
“…Flip chip packaging use a variety of interconnection technology to connect the active side of silicon chip to multilayered substrate using a process called die attachment [1]. In order to determine solder bump joint strength, ball shear test [2], ball pull test [3] and stud pull or die pull test [4] were used.…”
Section: Introductionmentioning
confidence: 99%